2006
DOI: 10.1007/s10646-006-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Turbidity mitigates lead toxicity to cladocerans (Cladocera)

Abstract: To test the hypothesis that sediment would have a synergistic effect on the toxicity of lead to cladocerans, we performed life table demography experiments with two pelagic (Diaphanosoma birgei and Moina micrura) and one littoral (Alona rectangula) cladoceran species. Life table demography experiments were conducted at three levels of turbidity (0, 17 and 170 NTU) and six concentrations of lead (as PbCl2) from 0 to 0.71 mg l(-1). Median lethal concentrations (LC50) forA. rectangula, D. birgei and M. micrura we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…The sensitivity of planktonic invertebrates towards heavy metals and pesticides depends on the physic-chemical conditions (Garcı´a-Garcı´ et al, 2006), the trophic status of the reservoir (Serra et al, 2010), the presence of detergent components (Sobrino-Figueroa, 2016), as well as on relat ion to the species (Wang et al, 2009;Sakamoto et al, 2010), their neonatal size (Vesela & Vijverberg, 2007), the number of single-celled algae (Sarma et al, 2000) which have mechanis ms for heavy metals detoxification (Macfie & Welbourn, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of planktonic invertebrates towards heavy metals and pesticides depends on the physic-chemical conditions (Garcı´a-Garcı´ et al, 2006), the trophic status of the reservoir (Serra et al, 2010), the presence of detergent components (Sobrino-Figueroa, 2016), as well as on relat ion to the species (Wang et al, 2009;Sakamoto et al, 2010), their neonatal size (Vesela & Vijverberg, 2007), the number of single-celled algae (Sarma et al, 2000) which have mechanis ms for heavy metals detoxification (Macfie & Welbourn, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…From the demographic study conducted here and from literature, it appears that in M. macrocopa the reproductive output is more metal-sensitive than mortality (Kammenga and Laskowski 2000). When quantifying the direct effects of toxicants to zooplankton, the duration of exposure , García-García et al 2006). Survivorship curves of cladocerans under favorable conditions show a Type 1 pattern in which at younger age groups the mortality is relatively low, but increases with time, due to physiological aging (Krebs 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Sediment levels were quantified gravimetrically using a Cahn 33 electrobalance and later converted into turbidity units (NTU) using a turbidimeter (Model Hanna, HI 93703). Previous work showed that sediment concentrations of 50 and 500 mg l À1 corresponded to 17 and 170 NTU, respectively (García-García et al, 2006).…”
Section: Methodsmentioning
confidence: 96%
“…Sediments may retain heavy metals by adsorption and thus lower levels in the water column. Consequently, turbidity levels in polluted waterbodies influence the toxicity of heavy metals to zooplankton (García-García et al, 2006).…”
Section: Introductionmentioning
confidence: 99%